Chemistry : the molecular nature of matter - Jespersen, Neil D.; Hyslop, Alison; Brady, James E., 1938- (John Wiley & Sons Ltd, 2022)
"The eighth edition of our textbook continues to emphasize the molecular nature of matter, strong problem solving, and clarity of writing that was the basis of the seventh edition of Chemistry: The Molecular Nature of Matter by Neil D. Jespersen and Alison G. Hyslop. In this edition, the relationship between the molecular level and the observable macroscopic properties of matter is presented in detail to reinforce and expand this fundamental concept. Learning chemistry requires work, and practical study skills are presented at the beginning of every chapter to help organize this work. Additional problem solving questions which integrate scientific practices, cross-cutting concepts and chemistry core ideas to relate the ideas presented in each chapter to the wider fields of science"--